A DIFFERENCE IN THE ARCHITECTURE OF THE SURFACE MEMBRANE OF NORMAL AND VIRALLY TRANSFORMED CELLS - Burger, Max M. (1969)
Several tissue culture cell lines that were transformed by a tumor virus have been found to react with an agglutinin, while under identical conditions their untransformed parent cell lines did not agglutinate. Since a short treatment of the parent cell line with low concentrations of proteases exposed the same agglutinin receptor sites in a fashion indistinguishable from the transformed cells, it is proposed that both viral and chemical transformation produce changes in the architecture of the membrane, identical to those of the proteases.